Shanghai : Developing a Green Electricity Scheme - Berrah, Noureddine; Heijndermans, Enno; Crowdis, Mark D. (World Bank, Washington, DC, 2014)
This report documents the experience of developing a green electricity scheme in Shanghai, China. It is intended to be a resource when replicating this effort in another city or country. The study consists of two parts. In Part 1, the general characteristics of both the framework for green electricity products and the market for green electricity products are presented. It also presents a summary of international experience, including a description of the green electricity concept and the market penetration in different countries, the characteristics of frameworks under which renewable electricity products are developed, and the characteristics of products developed under these frameworks. Different options for verifying and certifying frameworks are discussed on the basis of case studies. Finally, the required institutional framework and options for awareness creation and marketing are examined. In Part 2, the culminating framework and product characteristics for Shanghai are presented. The report provides a description of the scope of green electricity in Shanghai and it also describes the emerging Shanghai framework for green electricity products. At the end of Part 2, the report addresses the remaining issues concerning the development of the framework and the product. In addition, recommendations are provided for further development and the next steps.